A Review of the Civil Society Role in Exposing COVID-19 Corruption in Zimbabwe - Asuelime, Raquel A. (International Journal of Criminology and Sociology, 2021)
The paper examines the role of civil society in Exposing COVID-19 corruption in Zimbabwe. The essence is in the possibility of learning how civil society can adequately act as a watchdog against corrupt practices in the management of COVID-19 in Zimbabwe. As such, the paper presents documentary reviews and analyses of the connection between civil society and COVID-19-induced corruption. Using reviews of various literature, this paper analyses the role of civil society in challenging COVID-19 linked corruption in Zimbabwe since the advent of the pandemic in the country. The paper concludes that civil society was critical in exposing corrupt practices within government and the Health Ministry in particular. Principal among these cases was the Drax Scandal, the Jaji Scandal and the private hospital’s scandal. However, the extent of success varies with the type of corruption exposed and challenged. Relatedly, the endemic corruption problems in Zimbabwe explain why some civil societies aren’t simply proactive in exposing corrupt officeholders both in public and private health sectors via a nationwide campaign.